PENGARUH MODEL PEMBELAJARAN KOOPERATIF JIGSAW, KONVESIONAL DAN KEDISIPLINAN BELAJAR TERHADAP HASIL BELAJAR BAHASA INGGRIS - Aspari Aspari; Anggraini Anggraini (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The goal of this reaserach is to get data about the effect of cooperative learning and dicipline to the result of english learning at SMP Anugerah Abadi Pamulang Tangerang Selatan.The method of this research is experimental. The sample are 60 students that consist of 3O experimental class, and 3O control class that uses sampling technique, cluster sampling of konvensional learning. It can be proved by Fo=7,087 and sig = 0,010 < 0,05. The data analysis uses ANOVA in two line. The result of this research shows are: (1) there is signifcant effect of cooperative learning to the result of english learning student, (2) there is significant effect between students dicipline to the result of englsh learning, (3) there is effect of interaction that signficant between students dicipline and cooperativev learning to the result of english learning. This research has benefit to inprove the result of english learning by using cooperative learning style, as jigsaw, and students dicipine in the class, and optimalization students in learning English.